2011
DOI: 10.4081/reumatismo.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4-Ig interferes and downregulates the proinflammatory activities of rheumatoid synovial macrophages in monoculture

Abstract: n INTRODUzIONE L' attivazione della risposta linfocitaria T nell'immunopatogenesi dell'artrite reumatoide (AR) e delle malattie autoimmuni in generale, ha stimolato negli ultimi anni lo studio dei meccanismi immunologici di attivazione e costimolazione coinvolti in tali patologie, al fine di individuare possibili obiettivi terapeutici. CTLA4-Ig (abatacept) è una molecola di fusione ottenuta dall'unione del dominio extracellulare della molecola umana CTLA4 e della porzione Fc di un'immunoglobulina umana di clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Abatacept could also have an effect on osteoclast precursors, explaining the anti-erosive effects of abatacept [ 34 , 35 ], or on monocytes by modulating their migratory capacity [ 36 ]. Direct effects on macrophages have also been described resulting in decreased cytokine production and reduction of the inflammatory reaction [ 37 40 ], which could account for the beneficial effects in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Abatacept could also have an effect on osteoclast precursors, explaining the anti-erosive effects of abatacept [ 34 , 35 ], or on monocytes by modulating their migratory capacity [ 36 ]. Direct effects on macrophages have also been described resulting in decreased cytokine production and reduction of the inflammatory reaction [ 37 40 ], which could account for the beneficial effects in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, how they influence these expressions appears to differ between RASF and EC. Our recent data showed that CTLA4-Ig (abatacept), by interacting with the CD86 molecule on RA synovial macrophages, may induce reverse signaling with anti-inflammatory effects, involving NFkB intracellular pathway [1][2][3][4]. Objectives: We investigated the expression and production of TNFalpha on cultured human activated macrophages before and after in vitro CTLA4-Ig treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, increased levels of osteoclast precursors were found in untreated patients with RA compared to healthy donors and these levels normalized following treatment with CTLA‐4/Ig therapy . The migratory capacity of monocytes and ability of synovial macrophages to produce inflammatory cytokines in vitro were also attenuated by CTLA‐4/Ig . A direct role in for anti‐CTLA‐4 therapy in promoting joint damage is further strengthened by the finding that the levels of circulating osteoclast precursors and potential to form osteoclasts increased in patients receiving anti‐CTLA‐4 treatment (ipilimumab) for the treatment of melanoma.…”
Section: Immune Checkpoints In Iamentioning
confidence: 99%
“…13 The migratory capacity of monocytes and ability of synovial macrophages to produce inflammatory cytokines in vitro were also attenuated by CTLA-4/Ig. [17][18][19] A direct role in for anti-CTLA-4 therapy in promoting joint damage 17 is further strengthened by the finding that the levels of circulating osteoclast precursors and potential to form osteoclasts increased in patients receiving anti-CTLA-4 treatment (ipilimumab) for the treatment of melanoma. Together, these data support a mechanism where CTLA-4 blockade may promote the development of ICI-IA through two mechanisms: (a) the reactivation of autoreactive joint-specific T cells; and (b) direct effects on monocytes that promote the production of inflammatory cytokines, extravasation into tissues, and differentiation into osteoclasts.…”
Section: Ctla-4 Checkpointmentioning
confidence: 99%